A new species of Maldivea Gerlach 1962 (Nematoda, Oxystominidae) from Felidhoo atoll (Maldives, Indian Ocean) and an emended diagnosis of the sub-family and genus - Semprucci, F.; Balsamo, M. (Ecologica Montenegrina, 2019)
Maldivea Gerlach, 1962 is a possible endemic genus of the Maldivian archipelago for which only M. xarifae Gerlach, 1962 has been described so far. A new species of this genus, M. complexa n.sp., was recently found in Felidhoo atoll. It reveals a more complex structure of gubernaculum than in type species which appears to be divided into two pieces: one is a sort of long wing in the ventral part of the spicule and the other one, more complex, is characterized by several curved stripes which envelop the dorsal side of the spicule distal part. According to the present considerations, diagnoses of Paroxystomininae and Maldivea are emended.